2020
DOI: 10.1021/acsami.0c13307
|View full text |Cite
|
Sign up to set email alerts
|

M13 Bacteriophage-Assisted Morphological Engineering of Crack-Based Sensors for Highly Sensitive and Wide Linear Range Strain Sensing

Abstract: Despite their extraordinary mechanosensitivities, most channel-like crackbased strain sensors are limited by their poor levels of stretchability and linearity. This work presents a simple yet efficient way of modulating the cracking structure of thin metal films on elastomers to facilitate the development of high-performance wearable strain sensors. A net-shaped crack structure based on a thin platinum (Pt) film can be produced by coating an elastomer surface with M13 bacteriophages (phages) and consequently e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…Cycling performance was also evaluated, as shown in Figure 2g, a ≈270 cycle-sensor conditioning was observed, which is common for strain sensors. [48,54,55] The average level of peak ΔR/R 0 tends to be generally stable in the next 800 cycles. Certain fluctuations of the peak resistance change were observed, which may arise from cracking process and polymer substrate issue (Note 2, Supporting Information).…”
Section: The Overall Sensor Performancementioning
confidence: 99%
“…Cycling performance was also evaluated, as shown in Figure 2g, a ≈270 cycle-sensor conditioning was observed, which is common for strain sensors. [48,54,55] The average level of peak ΔR/R 0 tends to be generally stable in the next 800 cycles. Certain fluctuations of the peak resistance change were observed, which may arise from cracking process and polymer substrate issue (Note 2, Supporting Information).…”
Section: The Overall Sensor Performancementioning
confidence: 99%
“…[20,21] Conventional crack-based strain sensors typically consist of an elastomeric substrate to provide stretchability and a brittle conductive layer to generate cracks. [22][23][24][25] The constructed cracks in the brittle conductive layer cause a significant change in the resistance of the sensor. The generation of cracks in the conductive network improves the sensitivity of the sensor but unpredictable cracks evolution reduces the sensing range.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the conductive materials (metallic nanoparticles/nanowires, graphene, carbon nanotubes (CNTs), carbon black (CB)) with polymer matrix (Ecoflex, poly­(dimethylsiloxane) (PDMS), polyurethane (PU)) to form nanocomposite structures is one of the favorable methods to prepare flexible strain sensors. , The conductive materials play critical roles in determining the sensing performance. , Carbon fiber material, a type carbon-based nanomaterial, possessing the merits of good conductivity, high flexibility, and excellent stability, is a kind of desirable sensing material in flexible electronics. ,, Soaking, coating, spinning, and chemical vapor deposition (CVD) have been widely used to prepare conductive carbon fiber materials for flexible strain sensors . For example, Yin et al reported a flexible strain sensor based on reduced graphene oxide woven fabrics through the dip-coating method.…”
Section: Introductionmentioning
confidence: 99%